Figli della biotecnologia: Un’analisi delle tecniche di riproduzione assistita e delle sue conseguenze nell’ordinamento italiano, brasiliano e spagnolo - Burmann de Souza, Cimon Hendrigo (2023)
The purpose of this article is to discuss th e subject of assisted reproduction techniques and tackle the controversial issues arising from them. It intends to discuss the legal and ethical issues associated with the problem of infertility, through a comparative analysis of the Brazilian, Italian and Spanish legal systems, by highlighting some positive and negative aspects present in these laws. The most popular methods of assisted reproduction are artificial insemination, in vitro fertilization, gestation replacement, and ovum donation. The author analyzes the constitutionality of the interests of potential users of assisted reproduction, a pr ocess in which it is easy to lose sight of the interests of the most important person, the child. Another aspect of great importance in the current context of assisted reproduction is the ability to intervene in the genetic heritage of embryos, with eugenic objectives. It is necessary to refer to the beginning of human life, a subject of analysis required by all those who seek to investigate the ethical implicati ons of assisted reproduction.